Associations of plasma trimethylamine N-oxide, choline, carnitine, and betaine with inflammatory and cardiometabolic risk biomarkers and the fecal microbiome in the Multiethnic Cohort Adiposity Phenotype Study. Issue 6 (13th February 2020) - Fu, Benjamin C; Hullar, Meredith A J; Randolph, Timothy W; Franke, Adrian A; Monroe, Kristine R; Cheng, Iona; Wilkens, Lynne R; Shepherd, John A; Madeleine, Margaret M; Le Marchand, Loïc; Lim, Unhee; Lampe, Johanna W
Abstract: Background: Trimethylamine N -oxide (TMAO), a compound derived from diet and metabolism by the gut microbiome, has been associated with several chronic diseases, although the mechanisms of action are not well understood and few human studies have investigated microbes involved in its production. Objectives: Our study aims were 1 ) to investigate associations of TMAO and its precursors (choline, carnitine, and betaine) with inflammatory and cardiometabolic risk biomarkers; and 2 ) to identify fecal microbiome profiles associated with TMAO. Methods: We conducted a cross-sectional analysis using data collected from 1653 participants (826 men and 827 women, aged 60–77 y) in the Multiethnic Cohort Study. Plasma concentrations of TMAO and its precursors were measured by LC-tandem MS. We also analyzed fasting blood for markers of inflammation, glucose and insulin, cholesterol, and triglycerides (TGs), and further measured blood pressure. Fecal microbiome composition was evaluated by sequencing the 16S ribosomal RNA gene V1–V3 region. Associations of TMAO and its precursors with disease risk biomarkers were assessed by multivariable linear regression, whereas associations between TMAO and the fecal microbiome were assessed by permutational multivariate ANOVA and hurdle regression models using the negative binomial distribution. Results: Median (IQR) concentration of plasma TMAO was 3.05 μmol/L (2.10–4.60 μmol/L). Higher concentrations of TMAO and carnitine, and lower concentrations of betaine, were associated with greater insulin resistance (all P < 0.02). Choline was associated with higher systolic blood pressure, TGs, lipopolysaccharide-binding protein, and lower HDL cholesterol ( P ranging from <0.001 to 0.03), reflecting an adverse cardiometabolic risk profile. TMAO was associated with abundance of 13 genera (false discovery rate < 0.05), including Prevotella, Mitsuokella, Fusobacterium, Desulfovibrio, and bacteria belonging to the families Ruminococcaceae and Lachnospiraceae, as well as the methanogen Methanobrevibacter smithii . Conclusions: Plasma TMAO concentrations were associated with a number of trimethylamine-producing bacterial taxa, and, along with its precursors, may contribute to inflammatory and cardiometabolic risk pathways.